2007
DOI: 10.1021/ja070490w
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitized NO Release from Water-Soluble Nanoparticle Assemblies

Abstract: The photoluminescence from CdSe/ZnS core/shell quantum dots, modified to make them water-soluble by exchanging the surface ligands with dihydrolipoic acid, is partially quenched by adding the chromium(III) complex trans-Cr(cylcam)(ONO)2 + (1, BF4 - salt). This quenching, attributed to the formation of electrostatic assemblies due to ion pairing of 1 with the negatively charged QD surface, is accompanied by the release of NO owing to photosensitized reaction of the Cr(III) nitrito complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 24 publications
0
68
0
2
Order By: Relevance
“…Ford et al have designed a water-soluble nanocontainer for NO storage based on electrostatic assembly of DHLA-coated quantum dots and cationic dinitro complexes that uses energy transfer from the core to release NO. [104] In another approach, doping of Ag/Au nanoparticles serves as an antenna to absorb the energy from a laser beam of ''biologically friendly'' near-infrared (NIR) region, causing local heating and disruption of microcapsules. More recently, Bhatia et al designed multifunctional superparamagnetic nanoparticles for remote release of bound drugs (Fig.…”
Section: Nanoparticles As Drug Delivery Systemsmentioning
confidence: 99%
“…Ford et al have designed a water-soluble nanocontainer for NO storage based on electrostatic assembly of DHLA-coated quantum dots and cationic dinitro complexes that uses energy transfer from the core to release NO. [104] In another approach, doping of Ag/Au nanoparticles serves as an antenna to absorb the energy from a laser beam of ''biologically friendly'' near-infrared (NIR) region, causing local heating and disruption of microcapsules. More recently, Bhatia et al designed multifunctional superparamagnetic nanoparticles for remote release of bound drugs (Fig.…”
Section: Nanoparticles As Drug Delivery Systemsmentioning
confidence: 99%
“…As a result, various strategies have been designed to make such species more susceptible to longer wavelength excitation [45,48,51,52,54,76,80,85,90,[116][117][118][119]. With certain platforms, it has proved possible to achieve the NO release at longer wavelength by extending the conjugation of the ligand frame and by adding key substituent groups at strategic positions [65,85,90].…”
Section: Toward Longer Wavelength Activationmentioning
confidence: 99%
“…Subsequent studies have shown that the TPE technique with photoNORM conjugates can be used to deliver NO to cells [78] and to tissue [51]. Another strategy that has been applied is to use semiconductor quantum dots (QDs) and related nanoparticles as the light-gathering antenna to sensitize photoNORMs [51,80,119,122].…”
Section: Toward Longer Wavelength Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ford et al have developed a strategy for the photosensitized release of NO using CdSe/ZnS water-soluble quantum dots (QD) as antennae for energy transfer to trans-[Cr(cyclam)(ONO) 2 ] + , a known photochemical NO precursor [153,154]. Under irradiation, NO production is ∼15-fold enhanced with a QD/complex ratio of 10 −3 regarding the amount of NO produced from the trans-[Cr(cyclam)(ONO) 2 ] + solution only.…”
Section: Photochemistry Of Immobilized Compoundsmentioning
confidence: 99%